A Phytophthora sojae effector suppresses endoplasmic reticulum stress-mediated immunity by stabilizing plant Binding immunoglobulin Proteins - Maofeng Jing (Nature Portfolio, 2016)
Phytophthora pathogens manipulate host plant immune responses by secreting effector proteins into plant cells. Here, Jing et al. show that the Phytophthora sojaeAvh262 effector negatively regulates plant resistance by binding to host BiP proteins and suppressing ER-stress induced cell death